A Study on Girl Dropout in Community College of Kirtipur Municipality - Maharjan, Babita (Shahid Kirti Multidisciplinary Journal, 2024)
College dropout is one of the big problems in community college of Kirtipur. So, in this study, the researcher explores the social, financial and academic reasons of girls who quit their study at the college level. As education plays a vital role in holistic development of individual and nation, the issues of droping out of students from educational program are cricual area of research. While social, economic and academic factors may affect the students’ survival in the school, this study explores the particular reasons that cause girls college dropout at the undergraduate level. The research is based on constructive, interpretative qualitative ideas of mobile interview with open-ended questionnaires using purposive sampling methods with in-depth interviews using as tools to take the data. The findings of this study show that, social, economic and academic reasons influence the participants’ college dropout in under graduate level.